2020
DOI: 10.1097/md.0000000000018899
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review protocol of Tuina for children with acute bronchitis

Abstract: Background: Acute bronchitis (AB) is a common cause of childhood morbidity. Tuina, a kind of Chinese massage, is frequently used for the treatment of AB in children by traditional Chinese medicine doctors. However, there is no relevant systematic review show its effectiveness and safety. The study aims to evaluate the effectiveness and safety of Tuina for children with AB. Methods: The following electronic databases will be searched from the respective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Tuina (Chinese Massage), based on the viscera theory, meridian theory, 5 elements theory, is a kind of physical therapy of traditional Chinese medicine with a long history. [14] Many Tuina therapy for PD have been reported: spinal Tuina, [15] viscera Tuina [16] aromatherapy massage, [17] rhythmical massage therapy. [18] Acupressure therapy is also used to treat PD, such as pressing Sanyinjiao (SP6), [19] pressing Taichong (LR3).…”
Section: Description and Function Of Interventionmentioning
confidence: 99%
“…Tuina (Chinese Massage), based on the viscera theory, meridian theory, 5 elements theory, is a kind of physical therapy of traditional Chinese medicine with a long history. [14] Many Tuina therapy for PD have been reported: spinal Tuina, [15] viscera Tuina [16] aromatherapy massage, [17] rhythmical massage therapy. [18] Acupressure therapy is also used to treat PD, such as pressing Sanyinjiao (SP6), [19] pressing Taichong (LR3).…”
Section: Description and Function Of Interventionmentioning
confidence: 99%
“…Tuina, a massage remedy built on Chinese Medicine meridian theories and Zang-Fu organs, consolidates contemporary scientific knowledge, including anatomy, biomechanical role, and physiology. Previous randomized controlled trials (RCTs) have supported the effectiveness of Tuina for the treatment of different health conditions, such as acute bronchitis [ 4 ] and musculoskeletal disorders [ 5 , 6 ]. In relation to KOA, 2 systematic reviews have identified positive clinical effects of Tuina in improving the outcomes of patients with KOA [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous randomized controlled trials (RCT) have supported the effectiveness of Tuina for the treatment of different health conditions, such as musculoskeletal disorders [9,10] and acute bronchitis [11]. With regard to KOA, two systematic reviews have shown a positive clinical effect of Tuina in improving outcomes for patients with KOA [12,13].…”
Section: Introductionmentioning
confidence: 99%